Pectin extraction from garlic waste under dual acid condition. Issue 12 (20th September 2022) - Şen, Emine; Göktürk, Ersen; Uğuzdoğan, Erdal
Abstract: A novel approach for the extraction of pectin from garlic waste (peel, stem, and straw) was accomplished under dual acid solution conditions including two organic (citric acid [CA] and acetic acid [AA]), two inorganic (hydrochloric acid [HCl] and sulfuric acid [H2 SO4 ]) and six different mixtures of these acids (CA‐HCl, CA‐H2 SO4, CA‐AA, AA‐H2 SO4, AA‐HCl, and HCl‐H2 SO4 ) with 1/30 (v/w) solid–liquid ratio at 90°C in 90 min extraction duration. The effects of acid mixture on the yields and physicochemical properties of the extracted pectins from garlic waste were investigated. Applying different acid mixtures during the extraction process allowed to obtain pectin samples with controlled physicochemical properties and higher yields. The maximum pectin yield of 22.4% was observed in the extraction condition carried out HCl‐H2 SO4 (1/3 v/v) mixture. Extractions carried out under dual acid mixtures showed higher Gal‐A contents compared with the conditions where organic or inorganic acids were used alone. The extracted pectin samples were generally composed of high methoxyl pectin and their methoxyl contents are observed to be close to that of commercial citrus pectin. FT‐IR spectra results of the extracted samples from garlic waste confirmed the pectin structure compared with the FT‐IR spectrum of commercial citrus pectin. Results indicate that organic–inorganic dual acid mixtures could be used as an efficient extraction media for the controlled physicochemical properties and higher yields of pectin extraction. Considering that about 3.7 million tons of garlic waste is annually produced worldwide, it could be very beneficial to obtain pectin from these wastes as a useful product for the industry. Practical applications: Garlic waste was converted into a valuable product for the industry and used as an alternative pectin source. Applying organic–inorganic dual acid mixtures during the pectin extraction process from garlic waste allowed to obtain pectin samples with controlled physicochemical properties and higher yields. Extracted pectin samples showed higher Gal‐A contents compared with the conditions where organic or inorganic acids used alone. Obtained pectins were generally composed of high methoxyl pectins and their methoxyl contents are observed to be close to that of the commercial citrus pectin.